PENGARUH AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) TERHADAP TINGKAT KORUPSI PEMERINTAH DAERAH DI INDONESIA: STUDI KASUS PADA PEMERINTAH KABUPATEN BATANG - Suci Anggun Sari; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2019)
This study aims to test empirically the effect of local government financial reports accountability (LKPD) to the level of corruption in local government. Local government financial reports accountability (LKPD) based on the results of the inspection of the financial report by BPK that consists of a system of internal control and compliance with laws and regulations. Data were collected using questionnaire survey. The questionnaires were delivered to 175 employes of local government unit (SKPD) Semarang Regency specifically at financial/accounting departement. A total of 175 questionnaires 125 were returned and 120 can be proccesed. There are two hypotheses that were tested by using multiple regression analysis. The results of the analysis showed that the internal control system (SPI) that can effectively reduce the level of corruption. Meanwhile, compliance with the regulations does not affect to the level of corruption.